(untitled) (The Research of Medical Science Review, 2025)
Background: Non-elite athletes experience significant psychological distress, including depression, anxiety, and stress, often exacerbated by academic pressure, financial constraints, and performance expectations. Unlike elite athletes with structured mental health support, non-elite athletes navigate these challenges with limited resources, making them vulnerable to mental health disorders. Aims and Objectives: This study seeks to illuminate the burden of psychological distress among non-elite athletes in District Peshawar. By investigating the prevalence, contributing factors, and consequences of mental health struggles within this population, this research aims to bridge the gap between perception and reality. It advocates for a future where athletes are not only conditioned to endure but empowered to thrive—where their victories are not just measured in medals, but in the strength of their minds and the well-being of their souls. Methodology: This study explored psycho-social factors, dietary intake, and anxiety levels among non-elite athletes (aged 17–29 years) in District Peshawar. A sample of 100 participants including male and female athletes from the University of Peshawar was taken. The sample was selected using convenience and consent-based random sampling. Data was collected via a pretested questionnaire and assessed using the Depression Anxiety and Stress Scale (DASS-21). SPSS software was used for descriptive and inferential statistical analysis. Major Findings: Findings revealed notable gender differences in psychological distress. Moderate depression was more prevalent in males (61.5%), while 50% of females fell in the normal category. Severe anxiety was dominant in males (43.6%), while moderate anxiety was higher in females (63.6%). Stress levels remained low across both genders. Pearson’s Chi-Square test (p = 0.009) showed a significant association between depression and other variables in females. Conclusion: The study highlights the urgent need for gender-specific mental health interventions, emphasizing anxiety management for females and depression support for males. Structured psychological support programs, dietary awareness, and financial stability measures can enhance athletic performance and overall well-being.